Definitions for a common standard for 2D speckle tracking echocardiography: consensus document of the EACVI/ASE/Industry Task Force to standardize deformation imaging. (18th December 2014) - Voigt, Jens-Uwe; Pedrizzetti, Gianni; Lysyansky, Peter; Marwick, Tom H.; Houle, Helen; Baumann, Rolf; Pedri, Stefano; Ito, Yasuhiro; Abe, Yasuhiko; Metz, Stephen; Song, Joo Hyun; Hamilton, Jamie; et al.
Abstract: Recognizing the critical need for standardization in strain imaging, in 2010, the European Association of Echocardiography (now the European Association of Cardiovascular Imaging, EACVI) and the American Society of Echocardiography (ASE) invited technical representatives from all interested vendors to participate in a concerted effort to reduce intervendor variability of strain measurement. As an initial product of the work of the EACVI/ASE/Industry initiative to standardize deformation imaging, we prepared this technical document which is intended to provide definitions, names, abbreviations, formulas, and procedures for calculation of physical quantities derived from speckle tracking echocardiography and thus create a common standard.